The progress and prospect of assessment measures of uterine cavity function for infertility patients - Luping Zhang; Rui Ju; Xiangyan Ruan; Yinmei Dai; Husheng Wang; Fengyu Jin; Jing Jin; Muqing Gu; Jiaojiao Cheng; Yu Yang; Xin Xu; Thomas Roemer (Global Health Journal, 2021)
Objective: To explore the progress and prospect of evaluation methods for infertility patients. Methods: From September 2017 to December 2020, 199 cases of infertility patients who have accepted mini-hysteroscopy examination in the Department of Gynecological Endocrinology, Beijing Obstetrics and Gynecology Hospital, Capital Medical University. The patients who had primary ovary insufficiency, tubal infertility were excluded; patients with hysteroscopy contradiction, such as acute or sub-acute vaginal tract inflammation, endometrium lesion or endometrium carcinoma, severe cardiovascular, liver or kidney insufficiency were excluded. 40 patients were excluded and 15 patients lost follow up, 144 patients were eventually included in the analysis. The patient's age, body mass index, infertility etiology, preoperative and postoperative stimulate ovulation cycle, pregnancy state and pregnancy time were recorded. The effect of mini-hysteroscopy on ovulation induction cycle was analyzed in pregnant patients. Results: The average age of 144 patients was 32.10±4.67 years old. 96 (66.67%) patients were found to have intrauterine abnormalities, while 48 (33.33%) patients were found to have normal intrauterine cavity. 48 cases of pregnancy, accounting for 33.33%; the median and interquartile ranges [M (Q1, Q3)] of ovulation induction cycles before and after surgery were respectively [3 (0, 5)], [2 (1,3)], the difference was statistically significant (P < 0.05). Among the 48 pregnant patients, 32 of them had no structural lesions in hysteroscopy, the ovulation induction cycle of these patients before and after hysteroscopy were respectively [5 (0, 9)], [1 (0, 3)], the difference was statistically significant (P < 0.05). Conclusion: Uterine cavity evaluation is important for the assessments of fertility. As an advanced diagnosis instrument, mini-hysteroscopy can not only timely detect the intrauterine abnormalities of patients, but also with great application value in shorten the ovulation cycle in infertility patients and increase the pregnancy rate.